Innovative Work Behavior of Employees in The Government of West Tanjung Jabung District: The Effect of Organizational Support and Work Involvement, Mediated By Job Satisfaction - Juhandi Juhandi; Arthur Sitaniapessy; Neuneung Ratna Hayati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of organizational support and work involvement on employees' innovative work behavior, with job satisfaction as a mediating variable, at Regional Government Organizations in the Government of West Tanjung Jabung Regency. This study employed a quantitative approach involving 290 respondents. Data were collected through questionnaires that had experienced validity, reliability, comprehension testing, and instrument revision. The results showed that work involvement had a positive and significant effect on innovative work behavior, while organizational support and job satisfaction had no significant effect. In addition, organizational support and work involvement positively affected job satisfaction, but job satisfaction was unable to mediate the relationship among the variables. These findings indicate that improving employees' innovative work behavior is more effectively achieved through strengthening work involvement rather than increasing job satisfaction.